Is the Past Another Country? A Case Study of RuralUrban Affinity on Mudik Lebaran in Central Java - Vissia Ita Yulianto (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2011)
This study is to explore the relations between the urban and rural in terms of their social as well as cultural significance. Referring to the idea of David Lowenthal (1985:39-52) who has pointed out that the connection between the past and present rests on the fact that the past has been the source of familiarity, guidance, identity, enrichment and escapethe central idea of the paper is to suggest that this notion of a familiar past is a fundamental aspect of the culture of contemporary urbanised Central Javanese, who, during the Lebaran holiday, revisit their ancestral roots to retain a degree of autonomy against modernity or to return to their disappearing past as tourists, so to speak. The cultural practice of mudik becomes the interaction zone (Leaf, 2008) that provides opportunities for city dwellers to keep ties with their village of origin. Finally, the paper suggests that the continuing intimate interplay between the village and town proves that neither pastpresent nor ruralurban dichotomies are in categorically opposed realms; metaphorically speaking, they are not in different countries.